Developing a Conceptual Model for Antecedents of Resistance to Change towards Sustainable Construction Practices - Okoye, Peter Uchenna; Odesola, Isaac Abiodun (International Journal of Sustainable Development & World Policy, 2020)
This study developed a conceptual model of antecedents of resistance to change behaviours among construction professionals and contractors towards sustainable construction practices in Nigeria. Survey data gathered through a questionnaire were analysed with the aid of Statistical Package for the Social Science (SPSS) Software. Pearson Product Moment Correlation (r) and correlation significance test results revealed that human (r=0.973; p<.05), industry (r=0.996; p<.05), environment (r=0.984; p<.05), and policy (r=0.932; p<.05) factors were very strongly positively associated with resistance to change behaviours. Subsequently, a conceptual model of antecedents of resistance to change behaviours towards sustainable construction practices in Nigeria was empirically established. The correlation coefficient of determination result revealed that the direct effects of the conceptual model accounted for 94.67% of the variance in human factors, 99.20% of the variance in industry factors, 96.83% of the variance in environment factors, and 86.86% of the variance in policy factors. This suggested that professionals and contractors’ responses to change and resistance to change behaviours are accounting for a substantial proportion of the variance in any effort towards implementation of sustainable construction practices in Nigeria. Furthermore, this study highlighted the importance of multi-dimensionality of resistance to change and suggested that construction stakeholders should take note of these factors instead of general assumption where people tend to make judgments, based on observable behaviours. Finally, it recommended for rejuvenation of construction industry policies and integration of these factors that trigger behavioural resistance by the professionals and contractors in the sustainable construction practices policy intervention in Nigeria.